Satisfacción laboral para la retención del talento humano en el Ministerio de Transporte y Obras Públicas de la provincia Bolívar, año 2024. - Changoluisa Báez Alba Fernanda (2025)
The general objective of this research is to analyze the influence of job satisfaction on the retention of human talent in the Ministry of Transportation and Public Works of the Bolívar province, during the year 2024. It is based on the premise that the levels of job satisfaction They are directly related to the permanence of staff, which affects the operational efficiency of the institution. The methodology used combines an exploratory and descriptive approach, the survey and interview were used to collect primary information from employees, complemented with the analysis of secondary data, these methods allowed us to identify the perceptions of workers regarding their work environment and the factors that influence their decision to remain in the institution. The main results reveal that job satisfaction is influenced by factors such as the work environment, professional development opportunities and compensation policies; it was found that low levels of satisfaction increase the intention to leave the job. It is concluded that the improvement of working conditions and the strengthening of recognition policies are essential to increase the retention of human talent. It is recommended to implement strategies focused on professional development, effective communication and employee well-being to encourage their retention. Keywords: Talent, satisfaction, retention, compensation, working.